Pembelajaran Environmental Learning Pada Materi Kingdom Animalia - Arifin, Firda; Lestari, Pertiwi Indah; Nurhidayah (FKIP, Universitas Muslim Maros, 2025)
This study aims to determine whether there is an influence of Environmental Learning models in the kingdom animalia material on student motivation in class X SMAN 4 Maros. This research is a quantitative research with quasy experimental method with Pretest-Posttest Control Group Design. The number of samples is 66 students consisting of experimental and control classes taken at random. Data collection in this study is using a questionnaire / questionnaire, tests, and documentation. By analyzing the data used is the validity test, reliability test, normality test, and hypothesis testing. The results of the data analysis show that the Environmental Learning learning model has an effect on student motivation in class X SMAN 4 Maros. Researchers tested the instrument and obtained the calculation of the validity of the question questionnaire as many as 20 items that were declared valid and the reliability of the questionnaire as many as 20 questions whose results were reliable (consistent) also obtained the learning value of the experimental class students who had an average value = 86.06 and standards deviation = 6,819. While the control class has an average value = 71.82 and standard deviation = 11.027. Based on the t-test, Sig. (2-tailed) of 0,000 <0.05. The results of this study indicate that there are differences in the average learning value of students taught using the Environmental Learning (EL) learning model with the learning value of students taught with conventional learning models. So that the Environmental Learning model in the kingdom animalia material affects the motivation of students in class X SMAN 4 Maros.